2014
DOI: 10.1002/polb.23506
|View full text |Cite
|
Sign up to set email alerts
|

Control of all‐conjugated block copolymer crystallization via thermal and solvent annealing

Abstract: Control of the crystallization of conjugated polymers is of critical importance to the performance of organic electronics, such as organic photovoltaic devices, due to the effect on charge separation and transport, particularly for allpolymer devices. The block copolymer poly(3-dodecylthiophene)-block-poly(9,9-dioctylfluorene) (P3DDT-b-PF), which has matched crystallization temperatures for each block, is used to study the effects of processing history on resulting crystallization. For longer annealing times a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The increased control over the polymerization allows for a much better control over the molecular and, also, supramolecular structure. 13,[24][25][26][27][28] Applied to block copolymers with sufficiently differing blocks, this can result in a control over the microscopic morphology which is created by the microphases of the constituting blocks. In turn, a thermodynamically stable morphology can signicantly enhance the performance and lifetime of e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased control over the polymerization allows for a much better control over the molecular and, also, supramolecular structure. 13,[24][25][26][27][28] Applied to block copolymers with sufficiently differing blocks, this can result in a control over the microscopic morphology which is created by the microphases of the constituting blocks. In turn, a thermodynamically stable morphology can signicantly enhance the performance and lifetime of e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques give insight into different aspects of the morphology of the polymers. The X-ray diffraction techniques such as (Grazing Incidence) Wide Angle X-ray Scattering ((GI)WAXS), 24,26,30,31 Wide Angle X-ray Diffraction (WAXD), 27,31 Small Angle X-ray Scattering (SAXS) 31 and X-ray diffraction (XRD) 28,31,32 can identify the presence of different crystalline microphases by correlating the different observed refraction signals with the different microphases and these refraction signals also give insight in the lattices and stacking distances. The obtained stacking distances can this way directly be correlated with the different microphases that are present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The sequential crystallization of two conjugated blocks has been investigated with conjugated BCPs made of poly(dioctylfluorene) and P3HT, but the relative packing of the two blocks and their mutual influence on crystallization was not assessed. 25,26 Even more appealing are BCPs based on P3HT and the n- of P3HT-b-PNDIT2 in thin films was investigated using GIWAXS. [27][28][29] These studies demonstrated that both blocks can crystallize such that P3HT orients preferentially edge-on whereas PNDIT2 orients rather face-on on the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The assembly of nanostructured materials designed for specific functions is of increasing interest for a broad variety of applications as nanoparticles typically display extreme performances when measured on the microscopic scale. Hybrid nano-devices [1][2][3] are becoming ubiquitous in a vast range of applications, such as organic transistors, 4,5 organic solar cells, 6,7 and artificial photosynthetic systems. [8][9][10] The key advantage of combining nanostructured materials and conventional electronic platforms is that the nanomaterials respond in a very specific manner to external stimuli (e.g., the change of optical and electronic structure as a response to light or varying temperature).…”
Section: Introductionmentioning
confidence: 99%